Pediatric Posttonsillectomy Hemorrhage: Demographic and Geographic Variation in Health Care Costs in the United States. (August 2016) - Harounian, Jonathan A.; Schaefer, Eric; Schubart, Jane; Carr, Michele M.
Objective: To examine variations in management of pediatric posttonsillectomy hemorrhage and associated costs from a national third-party payer perspective. Study Design: The MarketScan database was analyzed for claims made for 30 days following tonsillectomy/adenotonsillectomy between 2008 and 2012 for privately insured children aged 1 to 17 years. Costs for management of postoperative hemorrhage by age, sex, and region were calculated in addition to total costs incurred for 30 days postoperatively. Setting: MarketScan database. Subjects and Methods: Database study. Results: A total of 305, 860 children were included. Overall, 0.3% had a postoperative bleed that required treatment but not surgical intervention or admission for hospitalization; 0.2% had one that required hospitalization; and 0.8% had one that required surgical intervention. The mean 30-day costs were 7660 for postoperative bleed that required surgery or hospitalization, 4580 for outpatient treatment, and 370 for no postoperative bleed. Children between 11 and 17 years old were most likely to have interventions for postoperative bleeding but had the lowest mean costs for them (7320 for hospital based, 3860 for outpatient). There were regional differences in costs for in-patient management of bleeds, with highest costs in the West, with a mean of 8850, versus the South, with a mean of 7160. Conclusions: There are geographic and demographic variations in managing pediatric posttonsillectomy hemorrhage and in the costs associated with management on a national level.